Effects of Chicken Manure Dose and Application Timing on the Productivity and Microbiological Safety of Lettuce (Lactuca sativa L.) - Undari, Desti; Melati, Maya; Kurniawati, Ani (Journal of Tropical Crop Science, 2026)
Organic lettuce is widely regarded as a healthier alternative because it is free of chemical contaminants. Chicken manure is commonly used as an organic fertilizer because of its high nutrient content, which is readily available to plants. However, applying manure poses a risk of pathogenic bacterial contamination. This study aimed to evaluate the effects of different chicken manure doses and application times, as well as their interactions, on lettuce (Lactuca sativa L.) productivity and microbiological safety. The experiment was conducted from March to May 2023 in Cianjur, West Java, using a factorial randomized block design (RBD) with three replications. Treatments included a control and two factors: (1) manure dose (10, 20, and 30 t/ha), and (2) application times (1, 2, and 3 weeks before transplanting). Microbiological analysis of harvested lettuce leaves was performed in the laboratory to assess contamination levels of Escherichia coli, Salmonella spp., and Shigella spp. Manure doses significantly influenced all growth and yield parameters but had no significant effect on quality variables, including flavonoid, nitrate, and total chlorophyll content. Application times showed no significant effect on any measured parameter. The interaction between dose and time was also not statistically significant for most variables. The highest productivity and marketable yield were observed at the 30 t/ha dose. Salmonella spp. was not detected in any samples; however, E. coli and Shigella spp. were present in all samples at levels exceeding the Indonesian National Standard (SNI) for food safety. In addition to the required dose of chicken manure, to minimize microbial contamination, fully decomposed manure is recommended for application, as it can be applied to land shortly before planting. The use of microbial-free water for washing vegetables is recommended, including in further research.